Василь Стус і українська народна творчість - Іщук, М. (Народна творчість та етнографія, 2005)
Folk songs played a great role in the formation of Vasyl Stus as a humanist and a patriot and he mentioned a lot the role that folk songs and folk culture are playing in the development of the nation's patriotism. The author of this articles describing the life and works of Vasyl Stus in the context of their connection to Ukrainian traditional music and folk songs. V.Stus's letters to his family were folk songs being mentioned and analyzed very actively. Special attention the author is paying to Stus's article "Something from the Thoughts of Our Predecessors about the National Question in Ukraine and it's Today's Life".